CT raw data (DICOM format) of coral mound core GeoB16310-3 from the Campeche coral mound province, MARIA S. MERIAN cruise MSM20-4 - Titschack, Jürgen; Timann, Christian; Lemke, Arne-Jörn (PANGAEA, 2025)
Whole rounds of coral mound gravity core GeoB16310-3 from a cold-water coral mound in the Campeche coral mound province, Gulf of Mexico, were scanned using a Toshiba Aquilion 64™ computer tomograph (CT) at the hospital Klinikum Bremen-Mitte, Germany, with an X-ray source voltage of 120 kV and a current of 600 mA. The CT image stacks have a resolution of 0.35 mm in the x and y directions and 0.5 mm resolution in the z direction (0.3 mm reconstruction interval). Images were reconstructed using Toshiba's patented helical cone beam reconstruction technique (TCOT).
Keywords: Campeche coral mound province; cold-water coral mound; Computed Tomography; Gulf of Mexico